Socio-Political Hate Speech: Manifestations of Language Malfunctions in the Perspective of Cyberpragmatics - R. Kunjana Rahardi; Septa Firda Utami (Universitas PGRI Sumatera Barat, 2024)
The presence of language on the internet that appears on various platforms forces language to be interpreted in a multimodal way. This research aims to: (1) Describe the forms of language functioning in socio-political hate speech in public spaces; (2) Describe the pragmatic meaning of language use in socio-political hate speech in public spaces. The data for this research is in the form of excerpts of speech on social media which contain forms of the early functions of language in socio-political hate speech. Data was collected using the listening method, not listening in the sense of listening, but listening in the sense of reading the text. The extralingual matching analysis method is applied with social, social, cultural and situational extralinguistic context matching tools. This matching analysis method is also applied by matching cybertext contexts, including cybertexts with visual, spatial, aural, gestural and linguistic dimensions. The steps in carrying out analysis include identification, classification, typification, and interpretation. This research produces findings in the form of manifestations of the form and pragmatic meaning of socio-political hate speech in public spaces. Form manifestations include slurs, harassment, propaganda, innuendo, cynicism, sarcasm, innuendo. Manifestations of pragmatic meaning include: insulting, insulting, defaming, insinuating, and ridiculing